Gynogenesis in Persian sturgeon (Acipenser persicus) and beluga (Huso huso) - Pourkazemi, M.; Mohseni, M.; Alipour, A.R.; Nowruzfashkhami, M.R.; Hassanzadeh Saber, M.; Bahmani, M.; Rezvani Gilkolaei, S. (Iranian Fisheries Science Research Institute, 2010)
The objective of the present study was to determine the possible production of Persian sturgeon (Acipenser persicus) and Beluga (Huso huso) gynogen/triploids and also to determine the most appropriate type of thermal shock and the duration of induced shock after fertilization. Persian sturgeon and Beluga spawners were collected from Guilan's sturgeon catch stations and transported to the Shahid Beheshti sturgeon hatchery for artificial breeding and restocking programs. Ovulated eggs and sperms were collected based on common procedures in hatcheries. In order to separate the seminal fluids and dilute the milts, sperms were centrifuged at 6000 rpm for 20 min. and seminal fluids stored in refrigerator for further use. Sperm motility was investigated. In order to determine the best duration for radiation, the milt was diluted (1:9) with immobilizing solution. Samples of diluted milt were placed for UV irradiation (UV lamp model UVG-54, 254 nm, made by UVP America) for 0.5, 1, 1.5, 1.45, 2, to 5 min. The motility of radiated sperms and controls were examined under the light microscope and the motility curve was drawn. For application of thermal shock two types of heat shock (32, 34 and 37°C) and cold shock (0±1°C) were used for duration of 2.5 and 60 min respectively. Both thermal shock were applied at 12, 15, 18 min after fertilization. Four experimental groups were designed including; normal eggs as control group and sperms without UV thermal shock), gynogenesis (Sperm irradiated with UV and thermal shock were applied), triploid (thermal shock without radiation by UV on sperm) and haploid group (without thermal shock but using irradiated sperm for fertilization). Verification of the success of treatments was assessed using genetic analysis on sturgeon larvae and fingerlings. In triploids the total surface area, volume of cells and nucleus as well as chromosome number were determined. To identify a gynogenetic larva, microsatellite markers were used to analysis specific loci by using primers designed for lake sturgeon. The results were analyzed using SPSS, Excell software. To determine the significant levels between various parameters and comparison between controls and various treatments, one way of Analysis of Variance (ANOVA) was used. Whenever the significant level was observed to determine its level a Duncan test were examined. Results of present study showed that the best duration for UV radiation on sperms of Beluga was 105-110 seconds. Average fertilization rate for control Beluga was 51%, while in heat shock group it was 2-5 % and in cold shock it was 44.6%. There was a significant difference in fertilization rate in cold shock group compared to heat shock group (P<0.05), however no difference was observed between 32 and 34°C treatments. The average survival rate of larvae in control group was 51%, while in heat shock treatment (32 and 34°C) it was very low close to zero. However in cold shock treatment the results was better and hatching percentage of larvae was between 30 -35%. Triploid treatment showed better results than gynogenesis group. A minimum triploid larvae obtained from heat shock was zero but using cold shock, the maximum number of 170 specimen was harvested. There was no significant difference in the number of larvae obtained between 32 and 34° C treatments (P<0.05). Although some difference was observed on large and small axes, surface areas and volume of red blood cells but no significant differences were observed between control and triploid groups (P 0.05). In the meantime, the chromosome number in triploid beluga was (3N=177±3) as compared to diploid 2N= 118±3, which indicated an extra set of chromosome (n=60) in triploid fish. Totally 26.6% of investigated fish was triploids. Microsatellite molecular markers clearly differentiate gynogenetic fish on the bases of allele inheritance of male and female parents, and were proven that this technique can clearly identify allelic inheritance of parents to offspring. In Persian sturgeon in compare to beluga a different results were observed. Heat shock (37°C) not present any positive results therefore has no application in induce gynogenesis on this species, also no significant difference was observed between 32 and 34°C treatment. Cold shock showed better results, especially when duration of UV radiation was adjusted to 105 seconds. Molecular analysis using microsatellite marker positively proved the gynogenetic offspring by counting the allelic inheritance. However Persian sturgeon as a tetraploid species (2N=240) has its difficulty on scoring the banding patterns. We highly recommend disomic primers application for allelic inheritance on gynogene Persian sturgeon.